February–May 2017. (31st August 2017) - Cranmer, Frank
Abstract : The EU (Notification of Withdrawal) Bill completed its passage through Parliament and received Royal Assent on 16 March. On 29 March, the United Kingdom's Ambassador to the European Union, Tim Barrow, handed over the Prime Minister's formal letter of notification under Article 50 of the Treaty on the European Union to the President of the European Council, thereby triggering the withdrawal process. Inevitably, however, the period since the last report was dominated not so much by Brexit as by the unexpected General Election.